An adult with adenocarcinoma of the epididymis – a case report - Paluchowska, Beata; Madej, Grzegorz; Wiechno, Paweł; Marczyński, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
Malignant neoplasms of the epididymis are very rare. The authors have found 24 cases of adenocarcinoma of the epididymis in the literature. The paper is a presentation of the case of adenocarcinoma of the epididymis. The authors have done review of the literature a avaliable in the MEDLINE.